Role of Bilirubin in Diabetic Vascular Complications: Can Bilirubin Predict More than Just Liver Disease? - Moon, Jun Sung (Diabetes & metabolism journal, 2015)
There are two isoforms of HO; HO-1 is a highly inducible form responsible for oxidative stress, and HO-2 is a constitutive form with an important role in brain and testes. On the contrary, a large Korean study found that higher bilirubin levels reduced the risk of diabetes and diabetic nephropathy [10]. Since an inverse correlation between bilirubin and coronary artery disease (CAD) was observed [11], many studies have consistently demonstrated a low concentration of bilirubin to be a risk factor for atherosclerotic CVDs. [...]a prospective study has indicated that bilirubin could be a protective and predictive biomarker for the development of cardiovascular events in patients with cardiac syndrome X, which is closely related to oxidative stress and vascular inflammation [13]. The mechanism underlying the antithrombotic functions of bilirubin could involve bilirubin reducing platelet activation as an antioxidant and inhibiting collagen-induced platelet aggregation and thrombus formation [16] in vitro.